The Implications of EFL/ESL Teachers' Emotions in Their Professional Identity Development - Cheng, Ling (Frontiers in Psychology, 2021)
The leading implementers of the curriculum and educational system are teachers, so the success and failure of the educational system depend mainly on its teachers. If teachers have an established professional identity, it leads to the success of the educational system. Professional identity, like other aspects of the teaching and learning process, is influenced by various factors. Investigating this concept requires identifying the factors affecting it. One of the most important factors that influence teachers’ professional identity is teachers’ emotions. Teachers’ emotions also can have a significant impact on teachers’ performance. After searching the databases, this review article examines the role of teachers’ emotions and their professional identities in English as a foreign language (EFL) classrooms. This review paper unpacks that factors such as teachers’ pedagogical beliefs, their positive and negative emotional experiences, their environmental and cultural factors, and their perceptions and expectations of these conditions could affect their emotions as well as their professional identity. Teachers’ identity is shaped through ongoing negotiation and interaction that encompasses their personal and professional lives. Taking these factors into account in teacher training courses might notify teachers of the challenges that they might have in their classrooms and provide them with practical solutions.